The surgical management and speech and swallowing rehabilitation of patients with advanced tongue cancer in South Africa - Leanie Engelbrecht; Anita Van der Merwe; Jan P Pretorius (AOSIS, 2006)
Advanced tongue cancer may have a devastating effect on a person's ability to speak and to swallow. Very little is known about the surgical management and speech and swallowing rehabilitation of persons with advanced tongue cancer in South Africa. Opsomming Gevorderde tongkanker het 'n geweldige impak op 'n persoon se vermoë om te praat en te sluk. Baie min inligting is bekend oor die chirurgiese behandeling en spraak- en slukrehabilitasie van persone met gevorderde tongkanker in Suid-Afrika. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.